The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.12714/egejfas.39.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of heavy metals after dredging in Mogan Lake, Turkey

Abstract: The lake management strategy of sediment dredging (removal) is periodically undertaken in shallow, eutrophic Mogan Lake, an important recreation area. This study aims to use certain indices - enrichment index (EF), contamination/pollution index (CF), degree of contamination (Cd), pollution load index (PLI), geoaccumulation index (Igeo), potential ecological risk index (Eri), integrated ecological risk index (PER), and mean probable effect concentration quotient (mPEC-Q) - to evaluate the state of sediment poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Metal elements threaten aquatic ecosystems, and their persistence in water bodies and ability to enter the food chain can be amplified, posing a potential risk to aquatic organisms [10]. Studies of metal elements in water, sediments, and soils have shown that Cd and Zn pose different levels of ecological risk [21][22][23]. Health risk assessments, which have been carried out since the 1980s, have linked environmental pollution to human health, quantitatively described the hazards from environmental pollution that affect the health of populations, and estimated the probability of the occurrence of hazards to humans from harmful factors.…”
Section: Introductionmentioning
confidence: 99%
“…Metal elements threaten aquatic ecosystems, and their persistence in water bodies and ability to enter the food chain can be amplified, posing a potential risk to aquatic organisms [10]. Studies of metal elements in water, sediments, and soils have shown that Cd and Zn pose different levels of ecological risk [21][22][23]. Health risk assessments, which have been carried out since the 1980s, have linked environmental pollution to human health, quantitatively described the hazards from environmental pollution that affect the health of populations, and estimated the probability of the occurrence of hazards to humans from harmful factors.…”
Section: Introductionmentioning
confidence: 99%